Engineering and war militarism, ethics, institutions, alternatives - Blue, Ethan. (Synthesis lectures on engineering, technology, and society, 2014)
This book investigates the close connections between engineering and war, broadly understood, and the conceptual and structural barriers that face those who would seek to loosen those connections. It shows how military institutions and interests have long influenced engineering education, research, and practice and how they continue to shape the field in the present. The book also provides a generalized framework for responding to these influences useful to students and scholars of engineering, as well as reflective practitioners. The analysis draws on philosophy, history, critical theory, and technology studies to understand the connections between engineering and war and how they shape our very understandings of what engineering is and what it might be. After providing a review of diverse dimensions of engineering itself, the analysis shifts to different dimensions of the connections between engineering and war. First, it considers the ethics of war generally and then explores questions of integrity for engineering practitioners facing career decisions relating to war. Next, it considers the historical rise of the military-industrial-academic complex, especially from World War II to the present. Finally, it considers a range of responses to the militarization of engineering from those who seek to unsettle the status quo. Only by confronting the ethical, historical, and political consequences of engineering for warfare, this book argues, can engineering be sensibly reimagined.